Chitosan-Based Nanocarrier Systems for Enhanced Antidiabetic Activity of Linagliptin: A Review - Barewar Gauri; Padole Nitin; Dhapke Pankaj; Dhoble Nilakshi; Baheti Jagdish (Asian Journal of Pharmaceutical Research and Development, 2026)
Diabetes mellitus, particularly Type 2 diabetes mellitus (T2DM), remains a major global health challenge due to persistent hyperglycemia, progressive β-cell dysfunction, and limitations of conventional oral therapies. Linagliptin, a selective dipeptidyl peptidase-4 (DPP-4) inhibitor, offers effective glycemic control with minimal risk of hypoglycemia and weight gain; however, its therapeutic potential is restricted by low oral bioavailability caused by poor intestinal permeability, P-glycoprotein efflux, and first-pass metabolism. Chitosan-based nanocarrier systems have emerged as promising strategies to overcome these barriers. Chitosan, a biodegradable, biocompatible, and Mucoadhesive polymer, enhances drug absorption, protects against enzymatic degradation, and provides sustained drug release. Various preparation methods, including ionic gelation, polyelectrolytic complexation, and emulsification-solvent evaporation, have been utilized to develop efficient linagliptin-loaded nanocarriers with improved encapsulation efficiency and controlled release profiles. These advanced delivery systems significantly improve linagliptin’s bioavailability, therapeutic efficacy, and patient compliance while reducing dosing frequency and systemic side effects. Additionally, targeted delivery approaches further optimize antidiabetic outcomes. This review highlights the formulation strategies, mechanisms, and therapeutic advantages of chitosan-based linagliptin nanocarriers, emphasizing their potential as innovative platforms for enhanced diabetes management and future clinical application.